Improved structural bonding adhesives
By using a combination of epoxy/elastic adduct, polymer particles, epoxy/diacid adduct and amine reaction products in the adhesive, the problem of insufficient assembly deformation and adhesion durability caused by the difference in thermal expansion coefficient is solved, and efficient adhesion performance and durability are achieved.
Patent Information
- Application Number
- CN201980072079.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-29
- Filing Date
- 2019-10-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-10-29
AI Technical Summary
When the existing adhesives bond between different materials, the assembly deformation is caused by the difference in thermal expansion coefficient, and the adhesion durability is insufficient in thermal, wet and corrosive environments, making it difficult to simultaneously improve fracture toughness and failure strain.
Using materials containing epoxy/elastic adducts, polymer particles, epoxy/diacid adducts and amine reaction products, the failure strain, adhesion, T-shaped peel strength and durability of the material are improved by optimizing component proportion and structural design.
The assembly stability is achieved in a high thermal expansion coefficient difference environment, and the adhesion durability and fracture toughness are improved, while maintaining appropriate tensile modulus and ease of distribution.
Smart Images

Figure CN112969738B_ABST
Abstract
Description
Technical Field
[0001] The present teachings are generally directed to activatable materials, methods of forming activatable materials, and methods of using activatable materials to adhere components of articles such as motor vehicles. The activatable materials provide improved adhesion to individual substrates (particularly when exposed to environmental stresses), and to improved adhesion between different substrates, and provide improved fracture toughness, improved strain to failure, and improved adhesion durability. Background Art
[0002] For many years, industry, especially the transportation industry, has been concerned with the bonding and reinforcement of articles such as motor vehicles. Of particular interest is the production of lightweight, energy-efficient vehicles in response to pressures from government regulations and other industry-wide demands. In turn, industry has developed a variety of activatable adhesive and sealing materials for use in providing such lightweight, improved fuel economy vehicles. One method of reducing vehicle weight includes replacing heavy components with counterparts composed of materials lighter than those currently used, such as replacing galvanized steel with aluminum or polymer composites.
[0003] Additionally, multi-material bonding (e.g., steel to aluminum) often requires different fastening devices than traditional welding. Dissimilar materials present significant challenges to traditional welding processes, so adhesives are often used instead of welding. To meet the needs of bonding dissimilar materials, these adhesives often need to have highly specific physical properties while also adhering to a variety of different substrates.
[0004] One problem with using such adhesives is that the coefficients of thermal expansion between components composed of different materials vary greatly. For example, the coefficient of thermal expansion of aluminum is approximately two times greater than that of steel. As a result, when the motor vehicle is heated to cure the coating and adhesive, problems such as delamination, warping, defect propagation, or other types of assembly deformation can occur. Therefore, a suitable adhesive material must have sufficient failure strain to compensate for the increased relative displacement due to the difference in the coefficients of thermal expansion of the materials being bonded to each other.
[0005] Another problem when dissimilar metals are in close proximity to one another is galvanic corrosion (e.g., the result of ion transfer that may occur when the interface of the two metals is exposed to an environment (e.g., a hot, wet, and corrosive environment). Therefore, suitable activatable materials must have sufficient adhesion durability in hot, wet, and corrosive environments.
[0006] Some other desirable properties of these materials include high fracture toughness, appropriate tensile modulus, improved washout resistance prior to activation (e.g., in its green state), and improved ease of dispensing when the material is on a surface prior to activation. These properties, including failure strain and adhesion durability, have a generally inverse relationship, with an increase in one followed by a decrease in the other. Therefore, providing simultaneous improvements in both properties is a significant challenge.
[0007] Thus, the present teachings are directed to providing a material having improved failure strain, adhesion, T-peel and wedge impact and / or durability after activation compared to existing activatable materials, while maintaining appropriate tensile modulus (e.g., a fairly consistent modulus over the temperature range of -40°C to 80°C), ease of dispensing, and washoff resistance (before activation). Summary of the invention
[0008] The teachings herein provide materials comprising an epoxy / elastomer adduct, polymer particles, from about 0.05 to about 20 weight percent of an epoxy / diacid adduct, and optionally an amine reaction product.
[0009] The material may have a T-peel of at least 14. The material may have a failure strain greater than 8%. The material may have a glass transition temperature defined by ASTM D 7028-07 of at least 80° C. The material may include an amine reaction product. The epoxy / elastomer adduct may include a polydisulfide polymer. The epoxy elastomer adduct may be present in an amount of at least about 5 wt % but less than about 50 wt % or even at least about 15 wt % but less than about 30 wt %. The polymer particles may be present in an amount of at least about 3 wt % but less than about 60 wt % or even at least about 27 wt % but less than about 32 wt %. The epoxy / diacid adduct may be present in an amount of about 0.2 wt % to about 15 wt % or even about 2 wt % to about 5 wt %.
[0010] The amine reaction product may be present in an amount of about 0.01 wt % to about 15 wt % or even about 0.5 wt % to about 5 wt %. The amine reaction product may be present in a sufficient amount so that the material exhibits a T-peel strength of about 6 N / mm to about 30 N / mm. The amine reaction product may be selected from 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, or a combination thereof. The amine reaction product may be adducted with an epoxy resin.
[0011] The material may contain phenoxy groups dissolved in an epoxy resin in the range of about 2% to about 10% by weight of the material. The material may contain a silane-modified epoxy resin in the range of about 8% to 18% by weight of the material.
[0012] The material may include a curing agent. The material may include a toughening agent. The epoxy component of the epoxy / diacid adduct may include bisphenol-F diglycidyl ether (DGEBF) epoxy resin. The diacid component of the epoxy / diacid adduct may be one or more of C18 or C36 diacids. The epoxy resin may be selected from bisphenol-F diglycidyl ether (DGEBF) epoxy resin, silane-modified epoxy resin, or a combination thereof.
[0013] The material may have a strain to failure of at least 16%.The material may have a modulus of at least 900 MPa.
[0014] The polymer particles may include a core modifier of polybutadiene, styrene-butadiene rubber or a combination thereof. The polymer particles may include core / shell rubber particles having an average size of about 100-200 nm. The polymer particles may be substantially free of agglomerated particles. The elastomer in the epoxy / elastomer adduct may be selected from polydisulfide polymers, CTBN, ETBN, Epoxonic 328 or any combination thereof.
[0015] The material may include a curing accelerator in the range of about 0.5% by weight to about 5.0% by weight of the material. The material may include a curing agent in the range of about 2% by weight to about 7% by weight of the material. The material may exhibit a tensile modulus of about 900MPa to about 1700MPa when cured. The material may exhibit a lap shear strength of at least about 20MPa when cured. When cured, the material may exhibit a T-peel strength of about 6N / mm to about 18N / mm.
[0016] The material may include one or more reinforcing components. One or more reinforcing components may be selected from silicon dioxide, diatomaceous earth, glass, clay (e.g., including nanoclay), glass beads or bubbles, carbon or ceramic fibers, nylon, aramid or polyamide fibers (e.g., Kevlar), pyrophyllite, sauconite, saponite, nontronite, wollastonite or montmorillonite. The material may include silicon dioxide and / or calcium-based reinforcing components. The silicon dioxide-based reinforcing component may be fumed silica.
[0017] The ratio of epoxy / elastomer adduct to reinforcing component can be about 1 to 30 parts of epoxy / elastomer adduct to about 1 to 4 parts of reinforcing component. The ratio of epoxy / elastomer adduct to reinforcing component can be about 15 to 30 parts of epoxy / elastomer adduct to about 1 to 2 parts of reinforcing component. The ratio of epoxy / elastomer adduct to epoxy / diacid adduct can be about 1 to 6 parts of epoxy / elastomer adduct to about 1 to 4 parts of epoxy / diacid adduct. The ratio of epoxy / elastomer adduct to epoxy / diacid adduct can be about 3 to 7 parts of epoxy / elastomer adduct to about 1 to 3 parts of epoxy / diacid adduct. The ratio of epoxy / diacid adduct to amine reaction product can be about 1 to 12 parts of epoxy / diacid adduct to about 1 to 3 parts of amine reaction product.
[0018] The teachings herein also relate to materials comprising less than about 30 weight percent of polymer particles, an epoxy / elastomer adduct, and an amine reaction product, wherein the polymer particles include core / shell rubber particles dispersed in an epoxy resin, wherein the core / shell rubber particles are present in a concentration of at least 20% of the polymer particles.
[0019] The material may include a silane-modified epoxy resin. The material may include a reinforcing component. The material may include an epoxy / diacid adduct. The material may have a failure strain greater than 8% and a modulus of at least 900 MPa. The material may include a curing agent. The material may contain about 15% to about 30% by weight of an epoxy / elastomer adduct. The material may have a failure strain of at least 16%. The material may have a modulus of at least 1100 MPa. The ratio of the epoxy / elastomer adduct to the silane-modified epoxy resin may be about 1 to 20 parts of the epoxy / elastomer adduct to about 1 to 13 parts of the silane-modified epoxy resin. The ratio of the epoxy / elastomer adduct to the reinforcing component is about 1 to 30 parts of the epoxy / elastomer adduct to about 1 to 4 parts of the reinforcing component.
[0020] The teachings herein also relate to the use of the materials described herein as adhesives. The teachings herein also relate to the use of the materials described herein for adhering components in transport vehicles. The teachings herein also relate to the use of the materials described herein for adhering steel to aluminum. The teachings herein also relate to the use of the materials described herein for adhering steel to polymer composites or for adhering aluminum to polymer composites.
[0021] The teachings herein also contemplate a method for adhering a first substrate to a second substrate comprising: applying the material of any of the preceding claims to the first substrate; then contacting the material with the second substrate after activating the material; and activating the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1Shown is a graph depicting storage modulus as a function of temperature for identifying glass transition temperatures for exemplary materials according to the present teachings. DETAILED DESCRIPTION
[0023] The explanation and description given herein are intended to make other persons skilled in the art familiar with this teaching, its principles and its practical application. The specific embodiments of this teaching set forth are not intended to be exhaustive or limit this teaching. The scope of this teaching should be determined with reference to the full scope of the equivalents given by the attached claims and these claims. The disclosures of all articles and references (including patent applications and publications) are incorporated by reference for all purposes. As will be collected from the attached claims, other combinations are also possible, and the claims are also incorporated by reference in this written description. Unless otherwise stated, percentages herein refer to weight percentages.
[0024] This application is related to U.S. Provisional Application No. 62 / 751,786 filed on October 29, 2018, the contents of which are incorporated herein by reference for all purposes.
[0025] The present teaching is based on providing improved materials (e.g., activatable materials) and articles containing the materials to illustrate. Activatable materials can help provide adhesion on the surface of a structure or to one or more structural members of an article. As used herein, the term activatable material includes any material that can be activated by environmental conditions or other conditions to melt, flow, solidify (e.g., thermosetting) or a combination thereof. For example, when exposed to conditions such as heat, pressure, chemical exposure or a combination thereof, the material can flow, melt, solidify or a combination thereof, etc.
[0026] The activatable material generally includes an epoxy / elastomer adduct, polymer particles, an epoxy / diacid adduct, an amine reaction product, a toughening agent, a phenoxy resin, a curing agent, a curing accelerator, and one or more reinforcing fillers.
[0027] The activatable materials of the present teachings can be applied to various articles to increase the structural integrity of parts or components of the articles. Examples of such articles include, but are not limited to, household or industrial appliances, furniture, storage containers, buildings, structures, etc. The activatable materials can be applied to parts of transportation vehicles, including ships, trucks, trains, airplanes, motor vehicles, etc. The materials can be used in motor vehicles, for example, in conjunction with the body or frame members (e.g., vehicle frame rails) of the motor vehicle.
[0028] The material can be formulated to include an adduct, which can be an epoxy / elastomer adduct. The epoxy / elastomer adduct imparts flexibility and the ability to produce a separate phase of the activatable material when cured and the ability to absorb energy during plastic deformation, and can impart the ability to produce phase separation. This phase separation can improve fracture toughness. Various adducts can be used in this teaching. The content of the epoxy / elastomer adduct can be up to about 75% by weight of the activatable material. The epoxy / elastomer adduct can be about at least about 5% by weight of the activatable material, more typically at least about 10% by weight, more typically at least about 15% by weight, and even more typically at least about 20% by weight. The epoxy / elastomer adduct can be about 75% or less by weight of the activatable material, more typically about 70% or less by weight, more typically about 65% or less by weight, and even more typically 60% or less by weight. The epoxy / elastomer adduct can be a combination of two or more specific adducts. The adduct may be a solid adduct, a liquid adduct, or a semisolid at a temperature of 23°C, or some combination thereof. The adduct may consist essentially of one or more adducts that are solid at a temperature of 23°C (i.e., at least 70%, 80%, 90% or more). The adduct (if solid) may be in dissolved form to facilitate simplified incorporation during mixing operations. The adduct may be used with polymer particles, such as core / shell materials, styrene-butadiene rubber (SBR) or polybutadiene (PBd), epoxy / diacid adducts, and amine reaction products, which may achieve desired adhesive properties and physical properties over a wide temperature range, even when relatively small amounts of the adduct are used.
[0029] The adduct itself typically includes about 1:5 to 5:1 parts epoxy resin to elastomer, more preferably about 1:3 to 3:1 parts epoxy resin to elastomer. More typically, the adduct includes at least about 10%, more typically at least about 20% and / or even at least about 30% elastomer, and also typically includes no more than about 60% elastomer, although higher or lower percentages are possible. Elastomer compounds suitable for use in the adduct can be thermosetting elastomers, but need not be. Exemplary elastomers include, but are not limited to, natural rubber, SBR (styrene-butadiene rubber), polyisoprene, polyisobutylene, PBd (polybutadiene), isoprene-butadiene copolymers, chloroprene rubber, nitrile rubber, butyl rubber, carboxyl terminated polymers (e.g., carboxyl functional butadiene-acrylonitrile), polydisulfide polymers, acrylic elastomers, acrylonitrile elastomers, silicone rubber, polysiloxanes, polyester rubber, diisocyanate linked condensation elastomers, EPDM (ethylene-propylene diene rubber), carboxyl terminated polymers, carboxyl terminated butadiene-acrylonitrile (CTBN), chlorosulfonated polyethylene, fluorinated hydrocarbons, etc. Examples of additional or alternative epoxy resins / elastomers or other adducts suitable for use in the present teachings are disclosed in U.S. Patent Publication 2004 / 0204551.
[0030] Examples of preferred adducts or preferred components for producing epoxy / elastomer adducts are epoxidized polydisulfide polymers, such as those sold under the trade name Thioplast TM G and Thioplast TM EPS is a product sold as such. A particularly preferred grade of epoxy / elastomer adduct is Thioplas t which is commercially available from Akzo Nobel. TM G10 and Thioplast TM EPS-80. Another example is Hypro TM 1300X13NA (CTBN), which can be obtained from Emerald Performance Commercially available, it is adducted with bisphenol F diglycidyl ether. Yet another example of a preferred epoxy / elastomer adduct is Hypro TM 1300X63 (ETBN (glycidyl esters of butadiene and butadiene-acrylonitrile)). Another example of a preferred epoxy / elastomer adduct can be prepared using Epoxonic 328.
[0031] Elastomer-containing adducts may be included to modify the structural properties of the activatable material, such as strength, failure strain, fracture toughness (G 1C), peel, bond durability, stiffness or other properties. CTBN can be particularly useful for developing adhesion to contaminated surfaces, especially adhesion to typical stamping lubricants in the automotive industry. The material can include a carboxyl terminated polymer adduct. The carboxyl terminated polymer adduct can impart an improved failure strain of greater than about 2% or even greater than about 3% to the activated material.
[0032] For illustrative purposes, Table A is prepared below to illustrate exemplary compositions for producing epoxy / elastomer adduct reaction products.
[0033] Table A
[0034]
[0035] In general, the activatable material preferably includes at least one type of polymer particles. Such polymer particles can be used to improve fracture toughness (G 1C ), peel resistance and impact resistance. As used herein, the term "polymer particles" is defined as particles comprising a polymer material. As with any other component of the present teachings, the term "polymer particles" may include one or more polymer particles. Various polymer particles may be used in the practice of the present teachings, and typically include one or more elastomers. Typically preferred polymer particles are at least 4% by weight of the activatable material, more typically at least 7% by weight, even more typically at least 10% by weight, still more typically at least 13% by weight, even more typically at least 16% by weight, and preferred polymer particles are less than 90% by weight of the activatable material, more typically less than 40% by weight, even more typically less than 30% by weight, although higher or lower amounts may be used in specific embodiments.
[0036] The polymer particles may include one or more core / shell polymers, which may be pre-dispersed in an epoxy resin. The method of forming a core-shell material in a liquid epoxy resin avoids agglomeration of the core-shell particles, which may be common for "dry" core-shell polymer particles (e.g., agglomeration may occur during the drying process). Examples of products prepared by this method may be described in one or more of the following U.S. patents: U.S. Patent Nos. 3,984,497; 4,096,202; 4,034,013; 3,944,631; 4,306,040; 4,495,324; 4,304,709; and 4,536,436. The polymer particles may be formed by an emulsion polymerization method. The method may include adding a solvent to the resin. Due to the incompatibility between the resin / solvent and water, when the core-shell particles move into the resin, water settles out of the material, resulting in reduced agglomeration. Alternatively, high-speed dispersion can effectively depolymerize the core / shell material. However, the surfactant may be retained after spray drying or coagulation of the core / shell material. This residual surfactant may be detrimental to the material's tolerance to environmental exposure conditions involving water, such as salt spray and humidity. Materials not exposed to environmental exposure conditions will generally not show a difference between dry and liquid, provided the dry material is sufficiently depolymerized. The polymer particles may include one or more core / shell polymers pre-dispersed in an epoxy resin, such as a bisphenol-A or bisphenol-F epoxy resin.
[0037] The term core / shell polymer as used herein can represent a polymer material, wherein the majority of the polymer material (e.g., greater than 30 wt%, 50 wt%, 70 wt% or more) can be composed of a first polymer material (i.e., a first or core material), which can be substantially completely encapsulated by a second polymer material (i.e., a second or shell material). As used herein, the first polymer material and the second polymer material can be composed of one, two, three or more polymers, which are combined and / or reacted together (e.g., sequential polymerization), or can be a part of a separate or identical core / shell system. The core / shell polymer should be compatible with the formulation, and preferably has a ductile core and a rigid shell that has favorable adhesion to other components of the activatable material.
[0038] The first and second polymer materials of core / shell polymer can comprise elastomer, polymer, thermoplastic material, copolymer, other components or their combination.The first polymer material, the second polymer material or both can comprise (for example, at least 70 wt %, 80 wt %, 90 wt % or more) one or more thermoplastic materials or can be substantially completely composed of (for example, at least 70 wt %, 80 wt %, 90 wt % or more) one or more thermoplastic materials.Exemplary thermoplastic materials include but are not limited to styrenes, acrylonitriles, acrylates, vinyl esters, polyamides, polyethylenes, PBd (polybutadiene), SBR (styrene-butadiene rubber) or their combination.
[0039] Examples of useful core-shell graft copolymers may be those copolymers in which hard compounds (e.g., styrene, acrylonitrile, or methyl methacrylate) are contained and can be grafted onto a core made of a polymer of a soft or elastomeric compound (e.g., butadiene or butyl acrylate). U.S. Patent No. 3,985,703 describes useful core-shell polymers whose core is made of butyl acrylate, but may be based on ethyl isobutyl, 2-ethylhexyl, or other alkyl acrylates or mixtures thereof. The core polymer may also include other copolymerizable compounds, such as styrene, vinyl acetate, methyl methacrylate, butadiene, isoprene, and the like. The core polymer material may also include a crosslinking monomer having two or more non-conjugated double bonds of approximately equal reactivity, such as ethylene glycol diacrylate, butanediol dimethacrylate, and the like. The core polymer material may also include a grafting monomer having two or more non-conjugated double bonds of unequal reactivity, such as diallyl maleate and allyl methacrylate.
[0040] The shell portion can be polymerized from methyl acrylates such as methyl methacrylate and optionally other (meth) alkyl acrylates and (meth) acrylates such as ethyl, butyl or mixtures thereof. Up to 40% by weight or more of the shell monomer can be styrene, vinyl acetate, vinyl chloride, etc. Additional core-shell graft copolymers that can be used in the embodiments of the present teachings are described in U.S. Pat. Nos. 3,984,497; 4,096,202; 4,034,013; 3,944,631; 4,306,040; 4,495,324; 4,304,709; and 4,536,436. Examples of core-shell graft copolymers include, but are not limited to, MBS (methacrylate-butadiene-styrene) polymers, which are made by polymerizing methyl methacrylate in the presence of PBd (polybutadiene) or polybutadiene copolymer rubber. MBS graft copolymer resins can typically have a SBR (styrene-butadiene rubber) core and a shell of an acrylic polymer or copolymer. Examples of other useful core-shell graft copolymer resins include PBd (polybutadiene), ABS (acrylonitrile-butadiene-styrene), MABS (methacrylate-acrylonitrile-butadiene-styrene), ASA (acrylate-styrene-acrylonitrile), all acrylics, SA EPDM (styrene-acrylonitrile grafted onto an elastomeric backbone of ethylene-propylene diene monomers), MAS (methacrylic acid-acrylic rubber styrene), and mixtures thereof.
[0041] Examples of useful polymer particles include, but are not limited to, those sold under the trade name Kane Ace TM Those polymer particles sold by Kaneka Americas Holding, Inc. are commercially available. Particularly preferred are Kane Ace TM Grades of MX-134 and MX-267 are sold under the trade names. The average size of the polymer particles may be no less than 50 nm and no greater than 300 nm. The polymer particles may be about 5% to about 30% by weight of the activatable material.
[0042] The material may include an epoxy / diacid adduct. The use of the term diacid may relate to any multifunctional molecule having two carboxylic acid moieties. Some diacid compounds are introduced into the epoxy backbone to increase the flexibility and toughness of the formulation and the ability to phase separate. The diacid component of the epoxy / diacid adduct may be a C8-C40 or higher diacid compound adducted with an epoxy. The epoxy component of the epoxy / diacid adduct may be DGEBF (bisphenol F diglycidyl ether). The diacid may be saturated or unsaturated. Preferably, the diacid is derived from an unsaturated fatty acid. Examples of preferred epoxy / diacid adducts are The esterification product of YDF-172LV (DGEBF) and C18 diacid. Another example of a preferred epoxy / diacid adduct is available from Emerald Performance Obtained DA323 (DGEBA and dimerized fatty acid adduct).
[0043] The adduct typically includes about 1:6 to 6:1 parts of diacid and epoxy resin, more preferably about 1:4 to 4:1 parts of diacid and epoxy resin. More typically, the adduct includes at least about 10%, more typically at least about 20%, even more typically at least about 40% of the diacid, and typically includes no more than about 60% of the diacid, although higher or lower percentages are possible.
[0044] The material may include an amine reaction product. Such a reaction product may be used to improve peel resistance and impact resistance without adversely affecting other properties such as lap shear, modulus measured by ASTMD 7029-07, ultimate strength, etc. The amine reaction product may include an amine portion and a hydrophobic portion. The hydrophobic portion may be aliphatic, cyclic, or a combination thereof. The hydrophobic portion may be C36 or less, C18 or less, C10 or less, or C4 or less. The amine reaction product may be selected to include one or more low molecular weight components. As a non-limiting example, the amine reaction product may include 1-naphthylamine, 2-naphthylamine, ethanolamine, phenylethylamine, oleylamine, or a combination thereof. The amine reaction product may be adducted with an epoxy resin. The amine reaction product may be adducted with a bisphenol-F epoxy resin, a silane-modified epoxy resin, or a combination thereof. Examples of suitable epoxy resins may include YDF 172LV (DGEBF). Another example of a suitable epoxy resin can include Epokukdo KSR-177 (a bifunctional silane modified epoxy resin). The amine reaction product can be adducted with the epoxy resin prior to addition to the material. The high molecular weight component can be selected so long as the detrimental effect on the viscosity of the material is minimized (e.g., so that the material can still flow as desired during application).
[0045] For exemplary purposes, Table B is prepared below to illustrate exemplary compositions for producing an amine reaction product with an epoxy resin.
[0046] Table B
[0047]
[0048] The material may include a toughening agent. The use of the term toughening agent may refer to a single toughening agent or a combination of multiple different toughening agents. Although other toughening agents may be used, preferred toughening agents include amine-modified, epoxy-modified, carbamate-modified polymers or any combination thereof. These polymers may include thermoplastics, thermosetting or heat-curable materials, elastomers, combinations thereof, and the like. These polymers may be modified with carbamates, aromatic or non-aromatic epoxy resins, and / or may be modified with bisphenol-F type, bisphenol-A type, combinations thereof, or other types of epoxy resins. Examples of preferred toughening agents (which may be phenol-terminated carbamate-based toughening agents) are EP 1820 (available from Innovative Resin Systems).
[0049] Examples of other preferred toughening agents are polyurethane modified epoxy resins sold under the trade names GME-3210 and GME-3220, which are commercially available from GNS Technologies. Without being bound by theory, it is believed that when polyurethane modified epoxy toughening agents are included, the activatable material can substantially maintain impact strength (e.g., impact resistance) at low temperatures while minimizing the reduction in glass transition temperature (Tg) (e.g., compared to other toughening agents). Other examples of preferred toughening agents are epoxy-terminated polyethers or amine precursors for producing epoxy-terminated polyethers, such as JEFFA MINE M series or SD series commercially available from Huntsman and DER 732 commercially available from Dow Chemical Company. Cashew nut shell liquid based toughening agents such as epoxidized liquid Cardolite NC-514 and Cardolite Lite 2513HP are also available toughening agents. Unless otherwise stated, all individual toughening agents discussed herein can be used alone or in combination with each other in the materials of the present invention.
[0050] Typically, the toughening agent is at least 1 weight percent of the material, more typically at least 2 weight percent, and possibly even at least 5 weight percent, but typically less than 50 weight percent, more typically less than 35 weight percent, and possibly even less than 20 weight percent, although higher and lower values are possible unless otherwise stated.
[0051] The materials described herein may include epoxy resins. Epoxy resins may be added to the activatable material to increase the adhesion, fluidity, or both of the material. An exemplary epoxy resin may be a phenolic resin, which may be a novolac type or other type of resin. An example of a suitable epoxy resin is YDF 172LV (DGEBF), available from Aditya Birla. Other preferred epoxy resin-containing materials may include modified epoxy resins. The epoxy resin may be a silane-modified epoxy resin or a silane-free epoxy resin. For example, a silane-modified epoxy resin may help allow the activatable material to adhere to a metal, such as aluminum. The silane-modified epoxy resin may be a reaction product between at least one epoxy resin and a silane compound. An example of a suitable silane-modified epoxy resin is Epokukdo KSR-177 (a bifunctional silane-modified epoxy resin) available from Kukdo Chemical. In addition, various mixtures of several different epoxy resins may also be used. The epoxy resin may be present in other formulation components, such as epoxy / elastomer adducts, polymer particle dispersions, and epoxy / diacid adducts. The concentration and type of epoxy resin present in the formulation components vary depending on the manufacturer and the specific grade. The epoxy resin may be present in the formulation components as an adduct, unreacted epoxy resin, or both.
[0052] The material may include a phenoxy resin component. Phenoxy resin is a high molecular weight thermoplastic condensation product of bisphenol A and epichlorohydrin and their derivatives. The phenoxy resin that can be used may have the following basic formula:
[0053]
[0054] Wherein, n is generally 30 to 100, preferably 50 to 90. Modified phenoxy resins may also be used. Examples of phenoxy resins that may be used are products sold by Gabriel Performance Products. Examples of suitable materials are PKHB, PKHC, PKHH, PKHJ, PKHP pellets and powders. Alternatively, phenoxy / polyester hybrids and epoxy / phenoxy hybrids may be used. In order to increase the yield of activatable material, the phenoxy resin is preferably supplied to the other components as a solution. Although any solvent may be used, it is particularly preferred to use a low molecular weight epoxy resin as a solvent because this may also help with adhesion properties during activation.
[0055] In certain embodiments, it may be desirable to include one or more thermoplastic polyethers and / or thermoplastic epoxy resins in the activatable material. When included, the one or more thermoplastic polyethers preferably comprise from about 1% to about 90% by weight of the activatable material, more preferably from about 3% to about 60% by weight of the activatable material, and even more preferably from about 4% to about 25% by weight of the activatable material. However, as with the other materials, more or less thermoplastic polyethers may be used depending on the intended use of the activatable material.
[0056] Thermoplastic polyethers typically include pendant hydroxyl moieties. Thermoplastic polyethers may also include aromatic ether / amine repeating units in their backbone. For a sample weighing 2.16 kg at a temperature of about 190° C., the thermoplastic polyethers of the present teachings preferably have a melt index of about 5 to about 300, more preferably about 30 to about 250 grams per 10 minutes. Of course, thermoplastic polyethers may have a higher or lower melt index, depending on their intended application. Preferred thermoplastic polyethers include, but are not limited to, copolymers of polyetheramines, poly(amino ethers), monoethanolamine and diglycidyl ethers, combinations thereof, and the like.
[0057] According to one embodiment, the thermoplastic polyether is formed by reacting a primary amine, a bis(secondary)diamine, a cyclic diamine, combinations thereof, and the like (e.g., monoethanolamine) with a diglycidyl ether or by reacting an amine with an epoxy-functionalized poly(alkylene oxide) to form a poly(amino ether). According to another embodiment, the thermoplastic polyether is made by reacting a difunctional amine with a diglycidyl ether or a diepoxy-functionalized poly(alkylene oxide) under conditions sufficient to react the amine moieties with the epoxy moieties to form a polymer backbone having amine linkages, ether linkages, and pendant hydroxyl moieties. Alternatively, the polymer may be treated with a monofunctional nucleophile, which may or may not be a primary or secondary amine.
[0058] Additionally, it is contemplated that amines (e.g., cyclic amines) having one reactive group (e.g., one reactive hydrogen) can be used to form thermoplastic polyethers. Advantageously, such amines can help control the molecular weight of the thermoplastic ether formed.
[0059] Examples of preferred thermoplastic polyethers and methods of forming the same are disclosed in U.S. Pat. Nos. 5,275,853; 5,464924 and 5,962,093, which are incorporated herein by reference for all purposes. Advantageously, the thermoplastic polyethers can provide the activatable material with various desirable characteristics, such as desirable physical and chemical properties for various applications, as further described herein.
[0060] One or more curing agents and / or curing agent accelerators can be added to the activatable material. The amount of curing agent and curing agent accelerator can be widely varied in the activatable material, depending on the required structural properties of the activatable material, etc. The exemplary range of the curing agent present in the activatable material is from about 2 wt % to about 7 wt %. The exemplary range of the curing agent accelerator present in the material is from about 0 wt % to about 5 wt %.
[0061] Preferably, the curing agent helps the activatable material to cure by crosslinking of polymers, epoxy resins or both. Available classes of curing agents are selected from the following materials: aliphatic or aromatic amines or their respective adducts, amidoamines, polyamides, alicyclic amines, anhydrides, polycarboxylic acid polyesters, isocyanates, phenolic resins (e.g., phenol or cresol novolac resins, copolymers such as those of phenol terpenes, polyvinylphenol or bisphenol-A formaldehyde copolymers, bishydroxyphenylalkanes, etc.) or mixtures thereof. Particularly preferred curing agents include modified and unmodified polyamines or polyamides, such as triethylenetetramine, diethylenetriamine, tetraethylenepentamine, cyanoguanidine, dicyandiamide, etc. Accelerators for curing agents (e.g., modified or unmodified ureas, such as methylenediphenylbisurea, imidazoles, or combinations thereof) can also be provided to prepare the activatable material.
[0062] Examples of suitable curing agents may be polyamide curing agents, such as those available from Evonik Resource Efficiency GmbH CG 1200 (micronized dicyanamide curing agent). Examples of suitable curing accelerators may be substituted urea accelerators, such as those available from Emerald Performance Obtained U-52M (phenyl substituted urea).
[0063] The activatable material may also include one or more reinforcing components. Preferably, the reinforcing component comprises a material that is generally non-reactive with other components present in the activatable material. It is contemplated that the reinforcing component may also impart properties such as strength and impact resistance to the activatable material.
[0064] Examples of reinforcing components include wollastonite, silica, diatomaceous earth, glass, clay (e.g., including nanoclays), glass beads or bubbles, carbon or ceramic fibers, nylon, aramid or polyamide fibers, etc. An example of a suitable filler can be fumed silica, such as available from Cabot Corporation. TS-720 (fumed silica treated with polydimethylsiloxane).
[0065] When used, the reinforcing component in the activatable material can be 10% or less to 90% or more by weight of the activatable material, but more typically about 20% to 55% by weight of the activatable material. According to some embodiments, the activatable material can include about 0% to about 30% by weight, more preferably slightly less than 10% by weight of the reinforcing component.
[0066] Other additives, agents or performance modifiers may also be included in the activatable material as desired, including but not limited to anti-UV agents, flame retardants, heat stabilizers, colorants, processing aids, lubricants, etc.
[0067] It is contemplated that most any additional chemical, material, or other substance may be added to the activatable material, provided that they are suitable for the activatable material and for the selected application of the activatable material.
[0068] It is possible that a specific combination and relative amount of one or more materials described herein can contribute to providing improved values for one or more tensile modulus, adhesion durability, T peel, failure strain or lap shear (all after activation). As another example, the combination of epoxy / elastomer adducts and epoxy / amine adducts can contribute to imparting improved strain failure rate and adhesion durability. The ratio of epoxy / elastomer adducts to epoxy / amine adducts is about 1 to 9 parts of epoxy / elastomer adducts to about 1 to 3 parts of epoxy / amine adducts. The ratio of epoxy / elastomer adducts to epoxy / amine adducts can be about 3 to 7 parts of epoxy / elastomer adducts to about 1 to 3 parts of epoxy / amine adducts. As another example, the combination of epoxy / elastomer adducts and silane-modified epoxy resins can contribute to imparting improved adhesion durability. The ratio of epoxy / elastomer adducts to silane-modified epoxy resins is about 1 to 10 parts of epoxy / elastomer adducts to about 1 to 7 parts of silane-modified epoxy resins. Another example is that the combination of amine adducts and diacid adducts can improve peel resistance and impact resistance.
[0069] When determining the appropriate components of the activatable material, it may be important to form the material so that it activates (e.g., flows, melts, solidifies, or otherwise changes state) only at the appropriate time or temperature. For example, in some applications, it is not desirable for the material to be reactive at room temperature or at ambient temperature in a production environment. More typically, the activatable material becomes activated to flow and produce adhesion at higher exposure temperatures. As an example, temperatures encountered in an automotive assembly plant, for example, may be suitable, particularly when the activatable material is processed with other components at elevated temperatures or higher applied energy levels (e.g., during a paint preparation step). The temperatures encountered in many coating operations (e.g., in a paint and / or electrophoretic curing oven) are, for example, in a range of up to about 250°C or higher.
[0070] The formation of the activatable material can be achieved according to various new or known techniques. Preferably, the activatable material is formed as a material having a substantially uniform composition. However, it is contemplated that various combination techniques can be used to increase or decrease the concentration of certain components in certain locations of the activatable material.
[0071] According to another embodiment, the activatable material can be formed by heating one or more components (e.g., polymer-based materials) that are generally more easily softened or liquefied to bring the components into a mixable state. Thereafter, the remaining components can then be mixed with the softened components. The materials can be compounded using melt processing operations such as twin screws, double arm mixers, or planetary mixers.
[0072] Depending on the components used, it may be important to ensure that the temperature of the components remains below certain activation temperatures that may cause the activatable material to cure prior to the expected cure time. Where it is desirable to maintain the activatable material at a lower temperature, it may be desirable to mix the components of the activatable material using pressure or a combination of pressure and heat to maintain the components in a semi-solid or viscoelastic state. Various machines have been designed to avoid applying heat, pressure, or both to the material.
[0073] After forming the activatable material, the material is typically applied to a surface and activated. When applied to a surface, the material can be in the form of a paste, film, solid extrudate, liquid or patch. The material can be applied by a robotic application device, which can be a robotic extrusion device.
[0074] It should be understood that, depending on the intended application, the activatable material can be applied and activated in different ways and at different times. Therefore, exemplary uses of the activatable material will be discussed below to illustrate preferred methods of application and activation of the activatable material. In particular, the activatable material can be used for reinforcement, adhesion, etc.
[0075] According to one embodiment, it is contemplated that the activatable material according to the present teachings can be used as a structural adhesive material. In such an embodiment, the material is typically activated and cured (e.g., at temperatures common to electrophoretic coating or automotive painting operations) to adhere to the first and second members. Contact with the attachment surfaces of the first and second members can occur before or during activation and curing of the material. Examples of structural adhesive applications are disclosed in U.S. Patent Application Serial Nos. 10 / 234,902; 10 / 386,287; 60 / 451,811, which are incorporated herein by reference for all purposes.
[0076] Certain activatable materials formed according to the present teachings have demonstrated a post-activation tensile modulus of greater than about 900 MPa, greater than about 1200 MPa, and even potentially greater than about 1500 MPa when measured according to the ASTM D638 Type IV test method. In addition, the activated activatable materials, particularly when provided as a solid, are generally less susceptible to rupture (e.g., crumbling, etc.).
[0077] Certain activatable materials formed according to the present teachings have exhibited post-activation lap shear strengths greater than about 30 MPa, greater than about 35 MPa, and possibly even greater than 40 MPa, when measured according to ASTM D5868.
[0078] Certain activatable materials formed according to the present teachings have exhibited post-activation strain to failure of greater than about 1%, greater than about 5%, greater than 8%, and even potentially greater than 15%. The strain to failure is measured by performing a tensile test (e.g., ISO 527) while using an extensometer to record the amount of deformation, which is then used to calculate the material strain.
[0079] Certain activatable materials formed according to the present teachings have exhibited glass transitions (T) greater than 80 degrees Celsius, greater than 85 degrees Celsius, and even greater than 90 degrees Celsius, when measured by ASTM D 7028-07. G ). The glass transition temperature determined by this test method (called the Dynamic Mechanical Analysis Tg or "DMA Tg") may be different from the glass transition temperature reported on the same test specimen by other measurement techniques. This test method is generally used to determine the upper service temperature of a composite material. Figure 1 The storage modulus as a function of temperature for exemplary materials of the present teachings is shown. The glass transition temperature is determined as the temperature at which the storage modulus begins to decrease more rapidly.
[0080] For exemplary purposes, Tables C through D are prepared below to illustrate two exemplary formulations for forming activatable materials.
[0081] Table C
[0082]
[0083] Table D
[0084]
[0085]
[0086] The comparative examples shown below demonstrate the changes in physical properties based on the inclusion / removal of certain components of the materials disclosed herein.
[0087] Table E
[0088] Sample 1 Sample 2 Sample 3 Sample 4 CTBN adduct 8.72 8.72 8.72 Silica 1.00 1.00 1.00 1.00 diacid adduct 2.50 3.50 5.00 Phenoxy resin 1.625 2.18 1.62 1.625 Polymer particles 10.87 11.61 10.87 10.25 Silane modified epoxy resin 11.30 15.70 13.55 12.98 Bisphenol F epoxy resin 46.215 41.18 41.27 42.705 Polyurethane-based toughening agent 5.44 6.00 5.44 5.44 Polysulfide adducts 5.00 7.00 5.00 Epoxy 328 adduct 5.45 5.00 5.45 5.45 Curing agent 5.97 5.97 6.20 5.97 Accelerator 0.76 0.76 0.78 0.76 pigment 0.10 0.10 0.10 0.10 total 100.00 100.00 100.00 100.00 Steel / steel lap shear strength (MPa)* 42.7 39.9 36.3 43.3 Steel / aluminum lap shear strength (MPa)** 41.6 39.5 38.8 41.5 Aluminum lap shear strength (MPa)*** 42.5 36.6 36.1 38.9 Steel / steel lap shear strength after 21 days of salt spray (MPa)* 32.1 33.8 30.2 21.1 Steel / aluminum lap shear strength after 21 days of salt spray (MPa)** 32.9 29.4 24.5 24.5 Aluminum lap shear strength after 21 days of salt spray (MPa)*** 30.2 25.2 14.8 19.7 T-peel (N / mm)**** 15.4 15.0 14.1 13.0 Peak stress (MPa) 36.5 35.3 33.2 36.1 Modulus (MPa) 1491 1580 1219 1561 Elongation(%) 21.5 14.0 15.7 12.8 Wedge impact @22℃ – Energy (J) 17.7 17.6 17.6 19.4 Wedge impact at 22°C - Average peel load (N / mm) 41.3 43.9 44.1 40.9 Wedge impact energy at -40℃ (J) 18.1 16.4 17.4 17.6 -Wedge impact at 40°C-Average peel load (N / mm) 43.5 38.0 42.0 37.0 Tg(℃) 82.1 90.9 103 95.7
[0089] *0.060”EG60 / 0.060EG60; **0.060”EG60 / 0.080”Alu 6061; ***0.080”Alu / 0.080”Alu 6061****0.030”EG60
[0090] Table F
[0091]
[0092]
[0093] *0.060”EG60 / 0.060EG60; **0.060”EG60 / 0.080”Alu 6061; ***0.080”Alu / 0.080”Alu 6061****0.030”EG60
[0094] As shown in Table E, Sample 1 includes all components but does not contain the amine reaction product. Sample 2 does not contain CTBN adducts and exhibits lower elongation and reduced wedge impact resistance at -40°C. Sample 3 does not contain polysulfide adducts and exhibits lower T-peel and reduced salt spray resistance for aluminum to aluminum bonding. Sample 4 does not contain any diacid adducts and exhibits reduced elongation.
[0095] As shown in Table F, compared with samples 6-10, sample 5 is a control sample that does not include an amine reaction product or a diacid adduct. Sample 6 includes a diacid adduct. Sample 7 includes both an amine reaction product and a diacid adduct. Sample 8 includes only an amine reaction product. Sample 9 includes both an amine reaction product and a diacid adduct, but does not contain polymer particles. Sample 10 includes both an amine reaction product and a diacid adduct, but does not contain a polysulfide adduct, a toughening agent, or an epoxy adduct (e.g., does not contain an elastomeric material). Sample 7 exhibits the best physical properties. The presence of an amine adduct shows a significant improvement in T-peeling. Due to the lack of polymer particles and an elastomer component, respectively, samples 9 and 10 both show generally reduced physical properties.
[0096] As used herein, unless otherwise stated, the present teachings contemplate that any member of a genus (list) can be excluded from a genus; and / or any member of a Markush group can be excluded from a group.
[0097] Unless otherwise stated, any numerical value described herein includes all values from lower values to higher values with one unit as increment, provided that there is an interval of at least 2 units between any lower value and any higher value. As an example, if the value of the amount, property or process variable (such as temperature, pressure, time, etc.) of the stated component is such as 1 to 90, preferably 20 to 80, more preferably 30 to 70, then the intended intermediate range value (such as 15 to 85, 22 to 68, 43 to 51, 30 to 32, etc.) is within the teaching of this specification. Similarly, each intermediate value is also within this teaching. For a value less than 1, a unit is considered to be 0.0001, 0.001, 0.01 or 0.1 as the case may be. These are only examples of specific intent, and all possible combinations of the numerical values between the minimum value and the maximum value listed are considered to be clearly stated in a similar manner in this application. It can be seen that the teaching of the amount represented as "parts by weight" herein also considers the same range represented by weight percentage. Thus, expression in a range of "'x' parts by weight of the resulting polymer blend composition" also contemplates teaching of the same recited amount range of 'x' as a percentage of the weight of the resulting polymer blend composition."
[0098] Unless otherwise specified, all ranges include both endpoints and all numbers between the endpoints. The use of "about" or "approximately" in connection with a range applies to both ends of the range. Thus, "about 20 to 30" is intended to cover "about 20 to about 30", including at least the specified endpoints.
[0099] The disclosures of all articles and references, including patent applications and publications, are incorporated by reference for all purposes. The term "consisting essentially of" used to describe a combination shall include the identified elements, ingredients, components, or steps, and such other elements, ingredients, components, or steps that do not materially affect the basic and novel characteristics of the combination. The use of the terms "comprising" or "including" used herein to describe a combination of elements, ingredients, components, or steps also contemplates embodiments consisting of or consisting essentially of the elements, ingredients, components, or steps.
[0100] Multiple elements, ingredients, components or steps can be provided by a single integrated element, ingredient, component or step. Alternatively, a single integrated element, ingredient, component or step can be divided into separate multiple elements, ingredients, components or steps. The disclosure of "one" or "an" describing an element, ingredient, component or step is not intended to exclude additional elements, ingredients, components or steps.
[0101] It should be understood that the above description is intended to be illustrative rather than restrictive. After reading the above description, many embodiments and many applications other than the examples provided will be apparent to those skilled in the art. Therefore, the scope of the present invention should not be determined with reference to the above description, but should be determined with reference to the full scope of the equivalents given by the appended claims and these claims. The disclosures of all articles and references (including patent applications and publications) are incorporated by reference for all purposes. The omission of any aspect of the subject matter disclosed herein in the appended claims is not a waiver of such subject matter, nor should it be considered that the inventor does not consider such subject matter to be a part of the disclosed inventive subject matter.
Claims
1. A material comprising: i) an epoxy / elastomer adduct present in an amount of at least 5% but less than 50% by weight; ii) greater than 0 wt% and less than 16 wt% of polymer particles, the polymer particles being core-shell materials; iii) 0.05 to 20 wt % of an epoxy / diacid adduct; and iv) 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or a combination thereof present in an amount of 0.01 wt% to 15 wt% and a phenoxy resin in the range of 2 wt% to 10 wt% of said material; v) a silane-modified epoxy resin in the range of 8% to 18% by weight of said material and a bisphenol F epoxy resin in the range of 40.205% to 64.815% by weight of said material; in, When cured, the material exhibits a strain to failure of at least 8% as measured according to ISO 527 and a tensile modulus of 900 MPa to 1700 MPa according to ASTM D638 Type IV test method.
2. The material according to claim 1, wherein The material has a T-peel of at least 14 N / mm.
3. A material according to any one of the preceding claims, wherein The material has a glass transition temperature of at least 80°C as defined by ASTM D7028-07.
4. The material according to claim 1, wherein The epoxy / elastomer adduct comprises a polydisulfide polymer.
5. The material according to claim 1, wherein The epoxy / diacid adduct is present in an amount of 0.2 wt % to 15 wt %.
6. The material according to claim 1, wherein The 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or a combination thereof is present in an amount sufficient for the material to exhibit a T-peel strength of 6 N / mm to 30 N / mm.
7. The material of claim 1, comprising a curing agent.
8. The material of claim 1 comprising a toughening agent.
9. The material according to claim 1 or 5, wherein The epoxy component of the epoxy / diacid adduct includes bisphenol-F diglycidyl ether epoxy resin.
10. The material according to claim 1 or 5, wherein The diacid component of the epoxy / diacid adduct is one or more of a C18 or C36 diacid.
11. The material according to claim 1, wherein The 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or a combination thereof is adducted with an epoxy resin.
12. The material according to claim 11, wherein the epoxy resin is selected from bisphenol-F diglycidyl ether epoxy resin, silane-modified epoxy resin, or a combination thereof.
13. The material according to claim 1, wherein The material has a failure strain of at least 16%.
14. The material according to claim 1, wherein The polymer particles include materials such as polybutadiene, styrene-butadiene rubber or a combination thereof.
15. The material according to claim 1 or 14, wherein The polymer particles include core / shell rubber particles having an average size of 100-200 nm.
16. The material according to claim 1 or 14, wherein The polymer particles are free of agglomerated particles.
17. The material according to claim 1, wherein The elastomer in the epoxy / elastomer adduct is selected from polydisulfide polymer, CTBN, ETBN, Epoxonic 328 or any combination thereof.
18. The material according to claim 1, wherein The material includes a cure accelerator in a range of 0.5 wt % to 5.0 wt % of the material.
19. The material according to claim 1 or 7, wherein The material includes a curing agent in the range of 2 wt % to 7 wt % of the material.
20. The material according to claim 1, wherein The material, when cured, exhibits a lap shear strength of at least 20 MPa.
21. The material according to claim 1, wherein The material, when cured, exhibits a T-peel strength of 6 to 18 N / mm.
22. The material of claim 1 comprising one or more reinforcing components.
23. The material according to claim 22, wherein The one or more reinforcing components are selected from silica, diatomaceous earth, glass, clay, glass beads or bubbles, carbon or ceramic fibers, aramid or polyamide fibers, pyrophyllite, sauconite, saponite, nontronite, wollastonite or montmorillonite.
24. The material of claim 1 comprising silica and / or calcium based reinforcement components.
25. The material according to claim 24, wherein The silica-based reinforcing component is fumed silica.
26. The material of claim 1 including a reinforcing component and wherein the ratio of the epoxy / elastomer adduct to the reinforcing component is from 1 to 30 parts epoxy / elastomer adduct to 1 to 4 parts reinforcing component.
27. The material of claim 1 including a reinforcing component and wherein the ratio of the epoxy / elastomer adduct to the reinforcing component is 15 to 30 parts epoxy / elastomer adduct to 1 to 2 parts reinforcing component.
28. The material according to claim 1, wherein The ratio of the epoxy / elastomer adduct to the epoxy / diacid adduct is from 1 to 6 parts epoxy / elastomer adduct to 1 to 4 parts epoxy / diacid adduct.
29. The material according to claim 1, wherein The ratio of the epoxy / elastomer adduct to the epoxy / diacid adduct is 3 to 7 parts epoxy / elastomer adduct to 1 to 3 parts epoxy / diacid adduct.
30. The material of claim 1, wherein The ratio of epoxy / diacid adduct to 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or combinations thereof is 1 to 12 parts epoxy / diacid adduct to 1 to 3 parts 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or combinations thereof.
31. A material comprising: i) greater than 0% and less than 16% by weight of polymer particles comprising core / shell rubber particles dispersed in an epoxy resin, the core / shell rubber particles being present in a concentration of at least 20% of the polymer particles; ii) an epoxy / elastomer adduct present in an amount of at least 5% but less than 50% by weight; iii) 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or a combination thereof present in an amount of 0.01 wt % to 15 wt % and a phenoxy resin in the range of 2 wt % to 10 wt % of said material; iv) 0.05 to 20 wt % of an epoxy / diacid adduct; v) a silane-modified epoxy resin in the range of 8% to 18% by weight of said material and a bisphenol F epoxy resin in the range of 40.205% to 64.815% by weight of said material; in, When cured, the material exhibits a strain to failure of at least 8% as measured according to ISO 527 and a tensile modulus of 900 MPa to 1700 MPa according to ASTM D638 Type IV test method.
32. The material of claim 31 comprising a reinforcing component.
33. The material of claim 31 comprising a curing agent.
34. The material of claim 31, wherein The material contains 15 to 30 wt % of the epoxy / elastomer adduct.
35. The material of claim 31, wherein The material has a failure strain of at least 16%.
36. The material of claim 31, wherein The ratio of epoxy / elastomer adduct to silane-modified epoxy resin is 1 to 20 parts epoxy / elastomer adduct to 1 to 13 parts silane-modified epoxy resin.
37. The material of claim 32, wherein The ratio of the epoxy / elastomer adduct to the reinforcing component is from 1 to 30 parts epoxy / elastomer adduct to 1 to 4 parts reinforcing component.
38. Use of a material according to any one of claims 1 to 37 as an adhesive.
39. Use of a material according to any one of claims 1 to 37 for adhering components in transport vehicles.
40. Use of a material according to any one of claims 1 to 37 for adhering steel to aluminium.
41. Use of a material according to any one of claims 1 to 37 for adhering steel to a polymer composite.
42. Use of a material according to any one of claims 1 to 37 for adhering aluminium to a polymer composite.
43. A method of adhering a first substrate to a second substrate, comprising: applying the material of any one of claims 1 to 37 to the first substrate; then contacting the material with the second substrate after activating the material; and activating the material.
44. The material of claim 1, wherein The epoxy / elastomer adduct is present in an amount of at least 15% but less than 30% by weight.
45. The material of claim 5, wherein The epoxy / diacid adduct is present in an amount of 2 to 5 wt%.
46. The material of claim 1, wherein The 1-naphthylamine or 2-naphthylamine or ethanolamine or phenylethylamine or oleylamine or a combination thereof is present in an amount of 0.5 wt % to 5 wt %.
Citation Information
Patent Citations
Structural hot melt material and methods
US20030069335A1
Epoxy / elastomer adduct, method of forming same and materials and articles formed therewith
US20040204551A1
Acrylate-styrene-acrylonitrile composition and method of making the same
US3944631A
Acrylic modifiers for polycarbonamides
US3984497A
Process for manufacture of acrylic core / shell polymers
US3985703A